DEMONSTRATION OF PSYCHOLOGICAL FACTORS FOR EXECUTING THE GYMNASTIC ELEMENTS (ACROBATIC) - Berisha, Milaim; Halili, Batjar (European Scientific Journal, ESJ, 2015)
In this study, we researched samples of 60 male students which were taken from the population of the High School Gymnasium “Gjon Buzuku” in Prizren, and the Gymnasium “Hamdi Berisha” in Malishevë. However, this school is well-known by majority of students in the Prizren Region. The subject of this research has been the execution of gymnastic (acrobatic) composure, which includes elements such as: excellent balance, verticals upon hands, gulping down forward, gulping down behind, turning aside, and turning with hands forward, respectively. The demonstration of psychological factors (level of confidence), includes fright, jealousy, confidence, and the great desire to achieve top results in order to execute the abovementioned composure elements. Gymnastic Elements executed by students were evaluated by three Physical Cultural and Sports Teachers conducted by the Chairman of the Commission (The teacher of physical sports education and the trainer of gymnastics). Therefore, the psychological status of students is identified by a questionnaire composed of seven questions, which include the psychological factors mentioned above (the questionnaire was formulated by a Psychologist).